(3GdeQGaYGJ GdEOGQjI (B:s (3ELQGAGJ QaY GdOYhi GdEOGQjI hJMVjQgG (B/s - (3HSjhfj, YHO GdQDha gGTes ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2017)
(3jJfGhd cJGH (B((3GdeQGaYGJ GdEOGQjI (B: (3ELQGAGJ QaY GdOYhi GdEOGQjI hJMVjQgG(B) (3hGdPj bGe HJCdjag (B((3YHO GdQDha gGTe HSjhfj(B) (3aj MhGdj (B(397) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdEOGQj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3Hjf GdCSS GdYGeI ddeQGaYGJ GdEOGQjI MjK YQa GdOYhi GdEOGQjI hHjf eUGOQ GdeQGaYGJ hGdbGfhf GdhGLH GdJWHjb Ydi GdeQGaYGJ GdEOGQjI hGdELQGAGJ GdSGHbI Ydi QaY GdOYhi hhVM GdWdHGJ GdeSJYLdI hWdH JbUjQ GdejYGO hELQGAGJ QaY GdOYhi GdEOGQjI hJMVjQgG(B. s
Keywords: (3GdbGfhf GdEOGQjs -- (3eUQs; (3GdOYhi GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdELQGAGJ GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs